Masonry works - Breakdown structure and specifications on ProNIC application - Pedro Meda (2014)
: Information organization is an essential aspect for the construction life cycle. ProNIC defines Protocol for Construction Information Standardization. It can be characterized as a database with technical information that provides functional and collaborative environment for project development. This paper is focused on exploring the information of this database, namely the one related with masonry works, and how it can improve the process outcomes. The information elements are explored evidencing their adequacy to the standards and the design best practices, towards the production of documents, as bill of quantities and technical specifications. Special insight is performed, evidencing the close relation of the database with ISO standards, namely ISO 12006-2, from the perspective of construction works and construction entities. Main functionalities, benefits and practical results are presented based on real work situations.